Peran Publik dalam Mendorong Kinerja Media Layanan Publik dalam Mewujudkan Watak Kepublikannya - Effendy, Rochmad; Yulistiowati, Irma Mufita; Wibowo, Aryo Prakoso (Jurnal Komunikasi Nusantara, 2020)
The publicness character of the Indonesia Republic Radio/RRI is both historical as well as legal necessity. RRI was born from the historical process as a struggle radio to seize and defend independence from colonialists. This true identity that is embodied in the spirit of public service ethos is getting stronger after the enactment of Government Regulation No. 11/2005 and 12/2005 concerning public service broadcasting and RRI public service broadcasting respectively. The duty of serving the needs and interests of the public must be the "spirit" which drives its whole operational activities of broadcasting and institutional governance. For this reason, various efforts have been made, such as improving governance and expanding the broadcast network area. To answer the demands of media digitization, the adoption of media convergence technology in the form of the launch of the RRI Play Go application has also been carried out. This has changed it from a public service broadcasting institution (PSB) to a public service media (PSM). Its public character as a public service broadcast radio must be put forward by placing the public as citizens (citizens) active participants both in the process of planning and implementing broadcast program content as well as media institutional governance. Through PSM, the interaction between media managers and citizens can be established. The process of involving citizens in the production process of media content is also easily facilitated. For this reason, their role in supervising and evaluating media management must be more substantial to ensure the public character of RRI. Based on this, this study aims to examine the form of public participation in supervising and evaluating broadcasting and media management of RRI. More specifically, what is the role of the Audience Council Forum Komunikasi Pemerhati of RRI Malang in carrying out this function.